Activities on acute mental health inpatient wards: A narrative synthesis of the service users' perspective. Issue 4 (5th February 2020) - Foye, Una; Li, Yan; Birken, Mary; Parle, Kayleigh; Simpson, Alan
Accessible summary: What is known on the subject?: Boredom is a big issue on inpatient mental health wards that is linked to poor patient satisfaction, feelings of frustration and increased incidents of self‐harm and aggression. This is even more so for people detained under the Mental Health Act. Where wards have a good range of activities, for example art, music, computer games, gardening and exercise, service users felt less bored and had improved well‐being. Over many years, studies have reported a lack of activities, especially during evenings and weekends. It has also been found that little is known about what activities service users want, or how activities might be meaningful for them. What the paper adds to existing knowledge?: This review found that very few studies have asked service users about what activities would be useful and why. By seeing what makes activities desirable and accessible, we can understand how to improve the experiences of service users on wards. Overall, these data help to understand what impact activities (or lack of activities) have on service users and staff experiences on these wards. What are the implications for practice?: Through identifying the activities most appreciated and engaged with by service users and by asking service users what activities they would like available, we can inform best practice guidance for the commissioning and provision of inpatient mental health care. This will enable service provider organizations to target their effort and resources on supporting good practice and to redirect resources from less useful activities. Abstract: Background: Concern about the lack of activities on mental health inpatient wards is long‐standing with reports consistently finding that service users receive insufficient access to a range of activities and report high levels of boredom. There is recognition that little is known about what service users want when admitted to inpatient wards. Aim: This review seeks to understand service users' experiences and views in relation to the provision and availability of activities, and to explore the perceived benefits and barriers to service users. Methods: We searched multiple databases (Scopus, MEDLINE, CINAHL, PsycINFO and Embase) for studies that evaluated activities on acute adult inpatient mental health wards. We identified 12 papers across a range of methodological designs from which the narrative synthesis has been analysed. Results: Findings show that the provision of activities is unsatisfactory for many service users, which in turn is related to increased boredom that has a negative impact on service users' well‐being. We explore the benefits and barriers to engagement, providing an insight into the aspects that make an activity important. Conclusion: There are few studies exploring the needs of service users regarding activity provision; therefore, there is limited knowledge about what is meaningful for individuals.